An algorithm for identifying mothball composition*. (14th September 2017) - Moss, Michael J.; Maskell, Kevin F.; Hieger, Michelle A.; Wills, Brandon K.; Cumpston, Kirk L.
Abstract: Introduction: Unintentional mothball ingestions may cause serious toxicity in small children. Camphor, naphthalene, and paradichlorobenzene mothballs are difficult to distinguish without packaging. Symptoms and management differ based on the ingested compound. Previous studies have used a variety of antiquated, impractical and potentially dangerous techniques to identify the mothballs. The goal of this study is to discover a simplified identification technique using materials readily available in an emergency department. Methods: Mothballs made of naphthalene and paradichlorobenzene along with camphor tablets were tested. Each material was tested both intact and after being fragmented to simulate a partially ingested mothball. Each of these six sample types were then immersed in 40 ml each of 11 fluids: water, 0.45% NaCl, 0.9% NaCl, lactated Ringer's, 5% dextrose in water, 5% dextrose in 0.9% NaCl, 50% dextrose in water, 8.4% NaHCO3, 3% H2 O2, 70% isopropanol, and 91% isopropanol. All tests were conducted in standard urinalysis sample cups to replicate available materials. Three toxicologists blinded to the identities of samples and solutions visually evaluated each sample. Observations included assessing response to immersion: sink, float, or dissolve. Results: All evaluators agreed in their description of 62/66 (94%) of the samples, with all four disagreements being on sinking and dissolving versus sinking only. A two-fluid algorithm utilizing 50% dextrose and water was sufficient to distinguish the sample types. Camphor will float in water while both paradichlorobenzene and naphthalene will sink. In 50% dextrose, both naphthalene and camphor will float while paradichlorobenzene will sink. Conclusion: Mothball materials can be distinguished by immersion in water and 50% dextrose. Limitations of this study include using camphor tablets as a substitute for mothballs given lack of availability.